Loss of the Coffin-Lowry syndrome-associated gene RSK2 alters ERK activity, synaptic function and axonal transport in Drosophila motoneurons - Katherina Beck; Nadine Ehmann; Till F. M. Andlauer; Dmitrij Ljaschenko; Katrin Strecker; Matthias Fischer; Robert J. Kittel; Thomas Raabe (The Company of Biologists, 2015)
Plastic changes in synaptic properties are considered as fundamental for adaptive behaviors. Extracellular-signal-regulated kinase (ERK)-mediated signaling has been implicated in regulation of synaptic plasticity. Ribosomal S6 kinase 2 (RSK2) acts as a regulator and downstream effector of ERK. In the brain, RSK2 is predominantly expressed in regions required for learning and memory. Loss-of-function mutations in human RSK2 cause Coffin-Lowry syndrome, which is characterized by severe mental retardation and low IQ scores in affected males. Knockout of RSK2 in mice or the RSK ortholog in Drosophila results in a variety of learning and memory defects. However, overall brain structure in these animals is not affected, leaving open the question of the pathophysiological consequences. Using the fly neuromuscular system as a model for excitatory glutamatergic synapses, we show that removal of RSK function causes distinct defects in motoneurons and at the neuromuscular junction. Based on histochemical and electrophysiological analyses, we conclude that RSK is required for normal synaptic morphology and function. Furthermore, loss of RSK function interferes with ERK signaling at different levels. Elevated ERK activity was evident in the somata of motoneurons, whereas decreased ERK activity was observed in axons and the presynapse. In addition, we uncovered a novel function of RSK in anterograde axonal transport. Our results emphasize the importance of fine-tuning ERK activity in neuronal processes underlying higher brain functions. In this context, RSK acts as a modulator of ERK signaling.